2016
DOI: 10.1007/s00705-016-3062-x
|View full text |Cite
|
Sign up to set email alerts
|

Fatality risks for nosocomial outbreaks of Middle East respiratory syndrome coronavirus in the Middle East and South Korea

Abstract: Middle East respiratory syndrome coronavirus (MERS-CoV) was first isolated in 2012. The largest known outbreak outside the Middle East occurred in South Korea in 2015. As of 29 June 2016, 1769 laboratory-confirmed cases (630 deaths; 35.6 % case fatality rate [CFR]) had been reported from 26 countries, particularly in the Middle East. However, the CFR for hospital outbreaks was higher than that of family clusters in the Middle East and Korea. Here, we compared the mortality rates for 51 nosocomial outbreaks in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
33
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 48 publications
6
33
1
Order By: Relevance
“… n.r. • Contacts - 20 primary, 39 first, 18 s, 7 third, 3 fourth generation • Secondary attack rate/10,000: 42 (95% CI: 33–54) Kim (2017) South Korea 2015 186 (111/75) 55 38/186 (19.9%) • Contacts - Hospital (99.4%) - Household (0.6%) - Community (0%) • Comorbidity - 29/38 fatalities had underlying disease Park (2017) [ 23 ] South Korea 2015 25 (13/12) 71 a (IQR: 38–86) 25/11 (44.0%) • Attack rate: 3.7% • Incubation period: 6.1 days Sha (2017) [ 29 ] Middle East area/ South Korea 2012–2016 683 (423/260) 50–60 (fatal), 38–46 (non-fatal) 182 (26.6%) (Middle East: 25.9%, South Korea: 13.8%) • Comorbidity - 67.9% in fatal, 22.2% in nonfatal cases • Incubation period - 4.5–5 days in Middle East area - 6 days in South Korea • Onset to confirmation - 8 days in fatal, 4 days in nonfatal in Middle East area - 4 days in fatal, 5 days nonfatal in South Korea • Onset to death - 11.5 days in Middle East area - 11 days in South Korea • Onset to discharge - 14 days in Middle East area - 17 days in South Korea Sherbini (2017) [ 32 ] Saudi Arabia 2014 29 (20/9) 45 ± 12 10 (34%) • Comorbidities - Diabetes (31%) - Chronic kidney disease (27%) • Symptoms to hospitalization: 2.9–5 days Assiri (2016) [ 36 ] Saudi Arabia 2014–2015 38 (28/10) 51 (range 17–84) 21/38 (55.3%) • Contacts - 13 HCWs - 15 were associated with 1 dialysis unit • Onset to death/discharge: 17 days (range 1.0–84.0) Cho (2016) [ 5 ] South Korea 2015 82 (53/29) 57 (patients and visitors), 38 (HCW) n.r. • Contacts - Patients: 40.2% - Visito...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… n.r. • Contacts - 20 primary, 39 first, 18 s, 7 third, 3 fourth generation • Secondary attack rate/10,000: 42 (95% CI: 33–54) Kim (2017) South Korea 2015 186 (111/75) 55 38/186 (19.9%) • Contacts - Hospital (99.4%) - Household (0.6%) - Community (0%) • Comorbidity - 29/38 fatalities had underlying disease Park (2017) [ 23 ] South Korea 2015 25 (13/12) 71 a (IQR: 38–86) 25/11 (44.0%) • Attack rate: 3.7% • Incubation period: 6.1 days Sha (2017) [ 29 ] Middle East area/ South Korea 2012–2016 683 (423/260) 50–60 (fatal), 38–46 (non-fatal) 182 (26.6%) (Middle East: 25.9%, South Korea: 13.8%) • Comorbidity - 67.9% in fatal, 22.2% in nonfatal cases • Incubation period - 4.5–5 days in Middle East area - 6 days in South Korea • Onset to confirmation - 8 days in fatal, 4 days in nonfatal in Middle East area - 4 days in fatal, 5 days nonfatal in South Korea • Onset to death - 11.5 days in Middle East area - 11 days in South Korea • Onset to discharge - 14 days in Middle East area - 17 days in South Korea Sherbini (2017) [ 32 ] Saudi Arabia 2014 29 (20/9) 45 ± 12 10 (34%) • Comorbidities - Diabetes (31%) - Chronic kidney disease (27%) • Symptoms to hospitalization: 2.9–5 days Assiri (2016) [ 36 ] Saudi Arabia 2014–2015 38 (28/10) 51 (range 17–84) 21/38 (55.3%) • Contacts - 13 HCWs - 15 were associated with 1 dialysis unit • Onset to death/discharge: 17 days (range 1.0–84.0) Cho (2016) [ 5 ] South Korea 2015 82 (53/29) 57 (patients and visitors), 38 (HCW) n.r. • Contacts - Patients: 40.2% - Visito...…”
Section: Resultsmentioning
confidence: 99%
“…One study using data from Saudi Arabia reported a 5.2 day incubation period [ 7 ], and another using data from multiple areas reported a 5.5 day incubation period [ 6 ]. Sha et al compared the incubation periods between the Middle East area and South Korea and reported 4.5–5 and 6 days, respectively [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported disease severity and mortality risk factor data from patients in the Middle East and South Korea. 11,12,21,[114][115][116][117] Ahmed and colleagues collected the daily information on MERS-CoV cases posted online by the Saudi Arabian Ministry of Health between Dec 2, 2014, and Nov 12, 2016, and reviewed 660 laboratory-confirmed cases of MERS. 114 They showed mortality at day 3 (13·8%), day 30 (28·3%), and overall (29·8%).…”
Section: Management Outcomes and Mortality Ratesmentioning
confidence: 99%
“…However, the health ministry of Saudi Arabia recommends pilgrims over 65 years; those with chronic diseases, such as heart, kidney, and respiratory diseases, diabetes, and immune deficiency; pregnant women; and children under 12 years, who are planning to attend the Hajj, to postpone their visit. 4 , 5 …”
Section: Introductionmentioning
confidence: 99%